MUTU BUAH JERUK KALAMANSI PADA BERBAGAI TINGKAT SERANGAN PENYAKIT KUDIS - Kusmea Dinata; Taufik Hidayat (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2019)
[FRUIT QUALITIES OF CALAMANSI UNDER DIFFERENT SCAB DISEASE SEVERITIES]. Citrus scab caused by Elsinoë fawcettii dan Elsinoë australis fungi is an important disease for calamansi lime. The pathogen can result creamy-yellowish, raised, rounded, corky scabs appear on the rind surface of the fruit that reduces marketabilityof the fruit. The objective of this  study was to evaluate the development and intensity of scab and their effects on the physical and chemical qualities of calamansi fruits. The observations were made on 30 fruit samples collected from farmer’s calamansi orchard for the development and intensity of disease symptoms, fruit appearances, juice content, and total soluble solids of the juice. The results showed that the pathogen began to attack on early fruit set phase. The intensity of the disease at the beginning of the observation was 11.06% and increased to 58.18% with an average rate of attack intensity of 14.54%. The disease reduced the fruit weight, fruit diameter, juice volume and total soluble solid levels.